Impact of Urbanization on Urban Heat Island and Urban Thermal Field Variance Index of Coastal City Surabaya, Indonesia between 2005 and 2020 - Foresty, Risma Salsabila; Putri, Rida Ayu Surya; Fadhilah, Ririn Nur; Fatin, Salma Kamiliya; Sulton, Muhammad Nur; Setyawan, Ahmad Dwi (Journal of Applied Informatics and Technology, 2025)
The city of Surabaya serves as the capital of East Java Province, Indonesia, experiencing the most intensive anthropogenic activities in this province. It has emerged as a primary destination for urbanization from various regions, leading to notable shifts in land use, vegetation, and Land Surface Temperature (LST). This study aims to analyzing the impact of urbanization on urban heat island and urban thermal field variance of coastal city Surabaya, Indonesia between 2005 and 2020. The findings reveal that Land Use Land Cover (LULC) changes significantly impact LST in Surabaya. Pearson Correlation results showed a positive correlation between Normalized Difference Vegetation Index, Urban Thermal Field Variance Index, and Urban Heat Island in 2005, 2011, 2015 and 2020 (p < 0.01). Alterations in land use contribute to elevated surface temperatures owing to diminished vegetation and increased built-up areas, thereby exacerbating ecological degradation and posing health risks to the urban environment. Consequently, implementing mitigation and adaptation measures becomes imperative to address the escalating urban heat phenomenon. Strategies such as augmenting green infrastructure and optimizing blue infrastructure are crucial for maintaining thermal equilibrium across the urban landscape.